Complete Simulation Models to Describe the Ductile-to-Brittle Transition of Steels for Arctic Applications - A Beremin-Gurson Approach - Scheide, Henrik Andre (NTNU, 2018)
The toughness of common structural steels is often affected by temperature changes where low service temperatures frequently promote brittle material characteristics. Low service temperatures often occur in the Arctic regions, and unexpected catastrophic failures may occur due to inadequate material characterisation. It is crucial to have a model with the highest level of accuracy to mitigate the risk of sudden brittle failure which in turn can precisely capture the material behaviour at shifting temperatures. The primary objective of the master s thesis is thus to develop a model which is able to describe the temperature dependence of fracture toughness in steels. The aim is to reduce the laboratory work needed to characterise the ductile-to-brittle transition regions. At lower temperatures, steels exhibit brittle behaviour and become susceptible to sudden brittle fracture without warning. Higher temperatures yield ductile behaviour with mechanisms such as void nucleation, void growth and void coalescence promoting ductile tearing and controlled ductile failure. The transition between the ductile and brittle regions exhibit both ductile and brittle behaviour and is crucial when steels are utilised in fluctuating and low service temperatures where sudden cleavage fracture may occur. Two Gurson-RKR models are initially developed in a preliminary study to describe the complete ductile-to-brittle transition and to visualise the ductile, transition and brittle regions. The RKR Criterion is a post processing routine for the ductile Gurson model and is used to predict brittle failure by considering critical stresses along the crack ligament with the critical opening stress ahead of the crack tip as both temperature dependent and independent. The Combined Gurson-RKR Model with temperature independent opening stress can describe the ductile-to-brittle transition by demonstrating increasing fracture toughness with increasing temperature. However, the results are somewhat conservative as the combined model highly ...